TX-001HR is associated with a clinically meaningful effect on severity of moderate to severe vasomotor symptoms in the REPLENISH trial. Issue 11 (November 2020) - Constantine, Ginger D.; Simon, James A.; Kaunitz, Andrew M.; Pickar, James H.; Revicki, Dennis A.; Graham, Shelli; Bernick, Brian; Mirkin, Sebastian
Abstract: Objective: The aim of the study was to evaluate the clinically meaningful effect of oral TX-001HR (17β-estradiol [E2]/progesterone [P4]) capsules on hot flushes severity (vasomotor symptoms [VMS] severity scale) using the patient-reported Clinical Global Impression (CGI). Methods: REPLENISH (NCT01942668) was a phase 3, randomized, double-blind, placebo-controlled, multicenter trial that evaluated TX-001HR in postmenopausal women (40-65 y) with a uterus. Those with frequent moderate to severe hot flushes (≥7/d or ≥50/wk) were randomized in a VMS substudy to daily E2/P4 (1/100, 0.5/100, 0.5/50, or 0.25/50 mg/mg), or placebo. Patients rated VMS severity from 1 (mild) to 3 (severe) and symptom improvements with the CGI. CGI results were an anchor in a nonparametric discriminant analysis to define clinically important differences (CIDs) and minimal CID in VMS severity at weeks 4 and 12. Results: In the VMS substudy ( n = 726), determined CID and minimal CID severity thresholds were reductions of 0.525 and 0.350 points at week 4, respectively, and 0.775 and 0.225 points at week 12. Significantly more women taking the two highest E2/P4 doses (1/100 and 0.5/100) versus placebo met CID severity thresholds at weeks 4 (40% and 44% vs 17%; P < 0.05) and 12 (56% and 48% vs 29%; P < 0.05). Conclusion: REPLENISH trial data demonstrated that E2/P4 1/100 and 0.5/100 provided clinically meaningful improvements in hot flushes severity in postmenopausal women. In conjunction with previously demonstrated clinically meaningful VMS frequency improvements, these data support oral E2/P4 1/100 and 0.5/100 for postmenopausal women with a uterus seeking treatment for moderate to severe VMS.